2013
DOI: 10.1021/jp405393d
|View full text |Cite
|
Sign up to set email alerts
|

Solute Diffusion in Ionic Liquids, NMR Measurements and Comparisons to Conventional Solvents

Abstract: Diffusion coefficients of a variety of dilute solutes in the series of 1-alkyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imides ([Prn1][Tf2N], n = 3, 4, 6, 8, and 10), trihexyltetracedecylphosphonium bis(trifluoromethanesulfonyl)imide [P14,666][Tf2N], and assorted imidazolium ionic liquids are measured using pulsed field gradient (1)H NMR. These data, combined with available literature data, are used to try to uncover the solute and solvent characteristics most important in determining tracer diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 94 publications
12
150
0
Order By: Relevance
“…12 We have also assumed hydrodynamic interactions (HI) are negligible in our simulations given the small sizes assumed for the diffusing particles. 40 In the event that larger particles are considered, for which HI may be significant, 41,42 one may resort to the Rotne-Pragner HI model, 43 which yields a position-dependent diffusion tensor for which the diagonal and off-diagonal terms represent self-and inter-particle diffusivities. In principle, this tensor could be used to parameterize the spatially dependent D (y) term of the HSE, under the assumption that the obstacles are fixed relative to the diffuser.…”
Section: Limitationsmentioning
confidence: 99%
“…12 We have also assumed hydrodynamic interactions (HI) are negligible in our simulations given the small sizes assumed for the diffusing particles. 40 In the event that larger particles are considered, for which HI may be significant, 41,42 one may resort to the Rotne-Pragner HI model, 43 which yields a position-dependent diffusion tensor for which the diagonal and off-diagonal terms represent self-and inter-particle diffusivities. In principle, this tensor could be used to parameterize the spatially dependent D (y) term of the HSE, under the assumption that the obstacles are fixed relative to the diffuser.…”
Section: Limitationsmentioning
confidence: 99%
“…44,50−52 In relation to the diffusional motion, Patra and Samanta have found that the diffusion coefficient of the solute molecule is affected by the heterogeneity of the solvation by using the fluorescence correlation spectroscopy. 53 The general trend of the relative volume dependence of the relative friction shown in Figure 6 indicates that the heterogeneous structure of ILs may not strongly contribute the diffusional motion of the solute molecule dissolved in ILs, as suggested by Kaintz et al 14 If the heterogeneous structure of ILs is a dominant factor, the dilution of [P 66614 ][NTf 2 ] with conventional liquid solvents may result in the different correlation with the case of pure ILs. To address this issue further, more detailed investigation using phosphonium or ammonium cation based ILs with different alkyl-chain lengths will be desirable together with the studies of conventional liquid solvents with longer alkyl chains.…”
Section: Methodsmentioning
confidence: 73%
“…Recently Kaintz et al reported a detailed collection of the translational diffusion coefficients in various kinds of ILs together with new data measured by PFG-NMR. 14,15 They evaluated the ratio of the diffusion coefficient determined experimentally to that estimated from the SE relation, and showed a good correlation of the ratio to the relative volume of the solute molecule to that of the solvent ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaintz et al reported self-diffusion of small concentrations of benzene in several ILs, including P 14,6,6,6 + /NTf − 2 . The ratio of diffusivities for C 6 H 6 to that for P 14,6,6,6 + was 28.2 at 298 K. 24 It is interesting to compare the values of the Arrhenius activation enthalpy for the shear viscosity E a,visc with the values of the self-diffusion coefficients for n-C 6 D 14 , P 14,6,6,6 + , and NTf − 2 obtained from PG-SE experiments, E a, PG−S E . We have done this for x C 6 D 14 = 0.5 to find that the values of E a,visc = 31.8 kJ/mol are quite similar to E a, PG−S E (NTf − 2 ) = 29.5 kJ/mol.…”
Section: Resultsmentioning
confidence: 88%